Awareness of cardiovascular risk factors among university students in Turkey. (2019) - Güneş, F. Esra; Bekiroglu, Nural; Imeryuz, Neşe; Agirbasli, Mehmet
Abstract: Aim: To determine the awareness of cardiovascular risk factors among university students in Turkey. Background: Cardiovascular disease (CVD) is the leading cause of death in developed countries. The use of tobacco products and unhealthy diet are prominent habits that increase the risk of CVD. Methods: Healthy university students ( n = 2450) aged between 18 and 22 years in Istanbul filled out the questionnaire about the awareness of CVD risk factors and participated in this cross-sectional study. They were asked several questions with regard to the importance of CVD risk factors. Findings: The leading responses for men and women were, respectively, high cholesterol (58.3; 72.3%), stress (58.8; 71.8%), hypertension (50; 64.2%), smoking (53.1; 58.7%), obesity (46.8; 64.3%), diabetes (41.7; 52.7%), inactivity (43.3; 47.8%), and CVD in family history (31.8; 44.4%). Unhealthy diet (9.7; 15.3%), exposure to second-hand cigarette smoking (24.4; 34%), and poor socioeconomic status (22.6; 22.3%) were also considered to be important. The study also revealed that men disregard the risk factors more frequently. Another comparison between body mass index groups revealed that obese subjects gave significantly lower importance to cardiovascular risk factors. Conclusion: Observations indicate that awareness levels of CVD risk factors have to be improved among university students. It is emphasized that primary healthcare workers are very important in the screening of CVD risk factors in an opportunistic and systematic way and in providing consultancy on changing risky behaviors (diet, smoking, etc.). Therefore, it is of utmost importance that primary healthcare workers make interventions to reduce the risk level by determining the CVD risk.